Pengembangan Aplikasi Pembelajaran Matematika Digital Interaktif Berbasis HTML 5 Pada Android Dan Windows Untuk Materi Transformasi Geometri Kelas IX - Andi Seppewali; Sulistia Rini; Supardi Muh Said (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This study aims to determine (1) the validity level of an interactive digital mathematics learning application product based on HTML5 on Android and Windows for geometry transformation material for grade IX, (2) student responses and teacher responses after using interactive digital mathematics learning applications, (3) implementation of learning using interactive digital mathematics learning application products, (4) the level of understanding of students' mathematical concepts after using interactive digital mathematics learning applications. This product development research design uses the 4D model, namely Define, Design, Development, Disseminate. The subjects in this study were 60 students of SMP Perguruan Rakyat 3 Jakarta grade 9. The results of the validity test for interactive digital mathematics learning application products through the alpha test on the five validators produced an average value of 4.45 (very valid). Furthermore, in the small group beta test each obtained results of 4.25 (very valid) and 4.73 (very valid). The results of the large group product validity test for student responses and teacher responses after use obtained results of 4.22 (very good), and 4.51 (very good). The results of the implementation of learning using interactive digital mathematics learning applications through the results of observations of the implementation of teacher learning activities and student activities obtained results of 92.53% and 90.80%, respectively. The results test of the students' ability to understand mathematical concepts showed that 81.67% of the students had achieved the minimum completeness criteria (KKM) score with a class average score of 82.